Cloning, expression, purification and crystallization of dihydrodipicolinate synthase from the grapevine Vitis vinifera - Atkinson, Sarah C. (International Union of Crystallography, 2011)

(untitled)
Dihydrodipicolinate synthase (DHDPS) catalyses the first committed step of the lysine-biosynthesis pathway in bacteria, plants and some fungi. This study describes the cloning, expression, purification and crystallization of DHDPS from the grapevine Vitis vinifera (Vv-DHDPS). Following in-drop cleavage of the hexahistidine tag, cocrystals of Vv-DHDPS with the substrate pyruvate were grown in 0.1 M Bis-Tris propane pH 8.2, 0.2 M sodium bromide, 20%(w/v) PEG 3350. X-ray diffraction data in space group P1 at a resolution of 2.2 Å are presented. Preliminary diffraction data analysis indicated the presence of eight molecules per asymmetric unit (V (M) = 2.55 Å(3) Da(−1), 52% solvent content). The pending crystal structure of Vv-DHDPS will provide insight into the molecular evolution in quaternary structure of DHDPS enzymes.